Optogenetics : past, present and future - Ádám, Éva; Hajdu, Anita; Nagy, Ferenc; Viczián, András (Acta Biologica Szegediensis, 2015)
The term ‘optogenetics’ was introduced into the scientific literature less than a decade ago by Karl Deisseroth, developer of pioneering optogenetic techniques, who defined optogenetics as “the combination of genetic and optical methods to achieve gain or loss of function of well-defined events in specific cells of living tissue”. Since then this new field of biology has become a very exciting and rapidly developing area producing hundreds of scientific publications. New methods and tools have been developed and long-sought answers found in these new experimental systems. Discussion and full elaboration of every optogenetic approach and application are beyond the scope of this review, instead, it gives a short insight to (i) how light can be used to manipulate the membrane potential of various cells; (ii) how light-sensitive proteins can be used to regulate targeted gene expression, and (iii) how controlled release or spatio-temporal targeting of certain molecules can be modulated by light. Besides, the most widely used light-sensor proteins, including their structure, working mechanism and their involvement in existing optogenetic applications are also discussed.